The Royal Proclamation Charter for the Company of Adventurers - Burns, Thea (Archivaria, 1998)
The text of the Royal Proclamation Charter for the Company of Adventurers (2 May 1670) is well known from printed sources. The rights and powers granted to the Hudson's Bay Company by the Charter, as well as challenges to these, have been thoroughly studied. Other features of this document are less familiar. These include the formal and informal administrative procedures which led to the physical production of the Charter, the Charter's documentary form, shape and size, and its language, calligraphy, decoration, and seal. This paper sets out to describe and comment on these features. RÉSUMÉ Le libellé de la Royal Proclamation Charter for the Company of Adventurers (2 mai 1670) est bien connu grâce aux sources imprimées. Les droits et pouvoirs octroyés à la Compagnie de la baie d'Hudson par la Charte ainsi que leur contestation out été étudiés en profondeur. D'autres caractéristiques de ce document nous sont moins familières. Cela s'applique aux procédures administratives formelles et informelles entourant la création de la Charte comme telle, son style documentaire, sa forme, sa taille, son langage, sa calligraphie, son ornementation et son sceau. L'article décrit et commente ces caractéristiques.